Explorasi Dan Identifikasi Tanaman Umbi-Umbian (Ganyong, Garut, Ubi Kayu, Ubi Jalar, Talas Dan Suweg) Di Wilayah Lahan Kering Kabupaten Madiun - ,, Wuryantoro; Arifin, M (JURNAL AGRI-TEK, 2017)
Diversification of food aims to realize the pattern of food diversification that takes into account the nutritional value and purchasing power of the people, improving the quality and human resources and food security through the availability of food in terms of quantity and quality of nutrition. The study aimed to explore and identification of tuber-producing crops in Madiun Regency for conservation purposes. Cluster analysis aims to classify accesion with color input parameters of stem, leaf shape, leaf color, shoot color, tuber color and tuber shape. The results showed that “ganyong” plants contained only one group, with distribution in five districts. Taro contained sixteen groups, with distribution in five districts. “Garut” there is one group, with distribution in five districts. “Gembili” there are two groups, with distribution in three districts. Cassava has five groups, with distribution in five districts. Sweet potato has five groups, with distribution in five districts. “Suweg” there are three groups, with distribution in five districts.Keywords : diversivication, clusters, tubers, dry land